مدى توافر متطلبات التعليم الالكتروني وتأثيرها في العملية - لبصير, هند (University of Eloued جامعة الوادي, 2021)
هدفت هذه الدراسة إلى الكشف عن مدى توافر متطلبات التعليم الالكتروني وتأثيرها في العملية التعليمية في ظل جائحة كورونا ،دراسة من وجهة أعضاء هيئة التدريس بالجامعة، وتم الاعتماد على المنهج الوصفي التحليلي، وتكونت عينة الدراسة من 262 أستاذ من عدة جامعات جزائرية، وتم استخدام استبيان إلكتروني بتصميم قوقل فورمس لجمع البيانات. توصلت الدراسة إلى أن هناك توفر نسبي لمتطلبات التعليم الالكتروني بالجامعة الجزائرية. أما عن اختبار الفرضيات فهناك أثر لأبعاد متطلبات التعليم الإلكتروني على وظائف العملية التعليمية عن بعد على ظل جائحة كورونا بالجامعة الجزائرية عند مستوى الدلالة ( 0.05)، وذلك من خلال الأثر الإيجابي لكل من المتطلبات المادية للتعليم الإلكتروني، الدعم التقني لإدارة الجامعة والاستعداد النفسي لأطراف العملية التعليمية على وظائف العملية التعليمية عن بعد، في حين جاء بعد كفاءات أعضاء هيئة التدريس بدون أثر على هذه العملية. وخلصت الدراسة بمجموعة من النتائج والتوصيات. This study aimed to reveal the availability of e-learning requirements and their impact on the educational process in light of the Corona pandemic, a study from the point of view of faculty members at the university. To achieve the objectives of the study, the descriptive analytical method was relied upon. The study sample consisted of 262 professors from several Algerian universities. The necessary data was collected using an electronic questionnaire designed by Google Forms. The study found that there is a relative availability of e-learning requirements at the Algerian University. As for hypotheses, there is an impact on the distance learning function of e-learning requirements in Algerian University at the level of significance ( 0.05), through the positive impact of both the physical requirements of e-education, the technical support of the university administration and the psychological readiness of the parties to the educational process for distance learning functions in the Corona pandemic, while the competencies of the teaching staff followed with no impact on the process. The study concluded with a set of findings and recommendations.
مقال